1996
DOI: 10.1007/bf02068072
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli heat-stable enterotoxin receptors

Abstract: Functional ST receptors are expressed in normal colonic tissue and primary and metastatic colorectal tumors but not by extraintestinal tissues in humans. Expression of ST receptors does not vary as a function of the metastatic site or grade of these tumors. Receptors expressed by colorectal tumors retain their characteristic function, with binding of ST coupled to activation of guanylyl cyclase. These studies support the suggestion that ST receptors represent a specific marker for human colorectal tumors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
76
0
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 55 publications
6
76
0
1
Order By: Relevance
“…14, 15 Here, we used in situ hybridization to determine the localization of GC-C mRNA in intestinal tissue obtained from Apc Min/1 mice. Robust GC-C expression in histologically normal colon is detectable within the glands of the crypt and on the surface epithelium (Fig.…”
Section: Fewer Polyps In Gc-c-deficient Min Micementioning
confidence: 99%
See 1 more Smart Citation
“…14, 15 Here, we used in situ hybridization to determine the localization of GC-C mRNA in intestinal tissue obtained from Apc Min/1 mice. Robust GC-C expression in histologically normal colon is detectable within the glands of the crypt and on the surface epithelium (Fig.…”
Section: Fewer Polyps In Gc-c-deficient Min Micementioning
confidence: 99%
“…13 By both biochemical and molecular methods, expression of GC-C has been widely observed in human primary and metastatic colorectal adenocarcinomas. 14,15 In contrast, expression of both guanylin 16,17 and uroguanylin 1 is absent or markedly decreased in colorectal tumors compared to adjacent normal tissue. Thus, a breakdown in normal signaling between GC-C and its ligands may occur in transformed tissue.…”
mentioning
confidence: 93%
“…In a recent issue of PNAS, Pitari et al (5) demonstrated the presence of a previously unrecognized STa͞GC-C-induced cGMP-dependent signaling pathway, through cyclic nucleotide-gated (CNG) channels and calcium, responsible for the antiproliferative action of bacterial enterotoxins on human colon carcinoma cells (5). Similar to results shown from previous studies (10), STamediated inhibition of DNA synthesis and cellular proliferation in colon cancer cells (17,19) was GC-C-dependent because controls using colon cancer cells devoid of GC-C (i.e., SW480 cells; ref. 19 (10) further demonstrated that this GC-C mediated inhibition of proliferation was associated with a reduced rate of DNA synthesis.…”
mentioning
confidence: 52%
“…As a result, subsequent loss of the initiation of GC-C signaling may represent one key mutational event underlying neoplastic transformation in the colon. However, intestinal GC-C and its downstream intracellular effector molecules are conserved in colorectal tumors (16,17), thus providing a means of restoring the signaling cascade associated with the tumor suppressor phenotype. In this manner, Forte and coworkers demonstrated that oral administration of uroguanylin suppresses the formation and progression of adenomatous polyps in the Min͞ϩ mouse animal model of colorectal cancer (13,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation